Delivering the Transforming Care programme: a case of smoke and mirrors?. (October 2019) - Taylor, John L.
Summary: The Transforming Care national plan for England to develop community services and close hospital beds for people with intellectual disabilities and/or autism was published in October 2015 and is due to finish in March 2019. In this editorial the key plan objectives are evaluated, with particular reference to people with intellectual disabilities and/or autism who offend or are at risk of offending. The conclusion is that, to date, the plan has failed to meet its targets to reduce the number of in-patients with intellectual disabilities and/or autism and to invest in community services, and the number of patients in independent sector beds is increasing. Declaration of interest: The author is employed by Northumberland, Tyne and Wear National Health Service Foundation Trust, however the opinions expressed in this article are the author's own and do not reflect the views of the Trust.